Triple systems with tripoints - Grannell M.J.; Griggs T.S.; Quinn K.A.S.; Stanton R.G. (Utilitas Mathematica, 2000)
We study the existence of triple systems in which there are i points such that any pair involving them must occur 3 times in the system. We call these TS(3,i,v) systems (Steiner triple systems could then be denoted as TS(1,v,v) systems). Those cases for which i < 6 are discussed.